The Iron Age and Romano-British settlement at Crick Covert Farm, Northamptonshire : excavations 1997-1998 - Hughes, Gwilym, (DIRFT ;, 2015)
This volume is the first of two reports on archaeological excavations undertaken ahead of the eastern expansion of Daventry International Rail Freight Terminal (DIRFT) which lies in the northern watershed region of Northamptonshire at its border with Warwickshire.